Mapping Research on Waqf History using Bibliometrix - Azzam, Hilmy Abdullah (International Journal of Waqf, 2024)
This study aims to see the development of research on the topic of "Waqf History" and research plans that can be carried out based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Waqf History" which comes from the Scopus database with a total of 150 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the bibliometric map of "Waqf History" research development in the world. The results of the study found that in bibliometric author mapping the authors who published the most research on the theme of "Waqf History" were Memiş Ş.E.; Liebrenz B; Abdullah A.S.; and Orbay K. Furthermore, based on bibliometric keyword mapping, there are 5 clusters with the most used words are development, institution, mosque, manuscript, charity, law, property, role, and land . Then, the topics of research paths related to Waqf History are Ottoman Empire and Waqf Management, Classical Waqf Principles, History of Waqf Activities as Charity, The Role of Scholars in Managing Waqf, and Waqf in Jerusalem during the Ottoman Era.